Change and innovation: an observable relationship in services? - Moreira, Marina Figueiredo (2016)
The connection between change and innovation is not always linear and there are not many studies on the subject in the area of services. This study aims to explain the link between willingness to change and innovation in services. The constructs Willingness to Change in Services and Innovation in Services have been analyzed. Two scales were applied in order to measure these constructs in a sample of 351 companies developing software services in Brazil. Two indices were generated: the Willingness to Change Coefficient – derived from the perception of technical staff and managers in relation to the variables of each factor on the Willingness to Change in Services scale – and the Innovation in Services Coefficient – derived from measures concerning the introduction of new or substantially improved software by companies and their impact. Linear regression analysis showed no significant correlation between Willingness to Change in Services and Innovation in Services. These findings can be explained by factors such as the dissonance between the constitutive logic of the Willingness to Change in Services and IS scales, since the former applies fully to the analysis of services while the latter derives from industrial indicators; the omission of phenomena that may act as mediators in the relationship; the nature of Change in Services, which could be related to other processes than those directly related to customer and provider, so that the agents of change are not considered in innovation measures and, therefore, not measurable on the Innovation in Services scale.